Physical characterization of plasmids determining synthesis of a microcin which inhibits methionine synthesis in Escherichia coli. - Perez-Diaz, J C (1980)
Plasmid deoxyribonucleic acid (DNA) isolated from each of three antibiotic-resistant clinical strains of Escherichia coli producing the same microcin showed multiple bands upon agarose gel electrophoresis. Transformants selected either for microcin resistance or ampicillin resistance yielded plasmid DNA corresponding in size to only one of the multiple bands. Plasmids, isolated from all three hosts, which determined microcin resistance and microcin production measured about 4 megadaltons by sucrose density, restriction enzyme, and contour length analyses; cleavage of the DNAs by each of eight restriction enzymes showed the same response, and DNA-DNA hybridization indicated complete homology. The antibiotic resistance plasmids of the three host strains were uniformly larger, were of different sizes, and showed different restriction enzyme cleavage patterns. One of these R plasmids (pCP106) also determined the synthesis of the same microcin, and DNA-DNA hybridization studies indicated an approximate 2.4-megadalton homology with the 4-megadalton microcin plasmid pCP101. The microcin plasmids were present at approximately 20 copies per genome equivalent and were nonconjugative, whereas the R plasmids had a copy number of about 1, were conjugative, and could mobilize the microcin plasmid. Microcin plasmid pCP101 showed replication properties similar to those of a number of small multicopy plasmids such as ColE1.